COMPARISON OF NEWBORNS FOR VAGINAL AND ABDOMINAL IN CHILDBIRTH BREECH - Chan, Elena (2015)
Objective: To verify if cesarean section ¡s the best delivery route in breech presentation. Design: Comparative prospective study done during 1998 at Sergio E Bernales Hospital, in newborns delivered by cesarean section or vaginally. Results: 58 newborns were delivered vaginally and 73 by cesarean section. Apgar at the first minute was significantly better (p<0,01) in those born by cesarean section (80,8%), and the depressed newborns (19,2%) had a quick recovery at 5 minutes (17,8%), different to those born vaginally who presented significantly higher rates of depression at 1 minute (53,4%) and 5 minutes (8,6%). Neonatal complications were significantly higher in the babies born vaginally (36,2% vs 20,5%) (p<0,01), and early neonatal mortality (61,0%) was also significantly higher (p<0,01) mainly due to asphyxia (3,4%). Conclusion: Breech presenting fetuses are born in better conditions and with less complications by cesarean section compared with those born vaginally. These results suggest the importance to evaluate perinatal benefits of cesarean section in breech presenting fetuses.